2011
DOI: 10.1007/s10578-011-0260-3
|View full text |Cite
|
Sign up to set email alerts
|

Can Parental Bonding Be Assessed in Children? Factor Structure and Factorial Invariance of the Parental Bonding Instrument (PBI) Between Adults and Children

Abstract: This study examined the factorial structure of the Parental Bonding Instrument (PBI) in the Greek population. Using confirmatory factor analysis different proposed models of the basic dimensions of PBI were evaluated. The results indicated that Kendler's three-factor (i.e. care, protectiveness and authoritarianism) solution was found to be more satisfactory than the other competing two-, three- and four-factor models. A second aim was the investigation of the factorial invariance of the PBI across different ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 41 publications
1
27
0
3
Order By: Relevance
“…The original PBI scale comprises of 25 items, an abbreviated version of the PBI, constructed by the authors of the article, consisted of 9 items. The abbreviated version was developed according to Kendler's three-factor solution and the parameter estimates of each item (Tsaousis et al, 2012). The three items with the highest parameter estimates were selected for each factor: care ("Spoke to me in a warm and friendly voice", "Enjoyed talking things over with me", "Frequently smiled at me"), protectiveness ("Tried to control everything I did", "Tried to make me feel dependent on her/him", "Was overprotective of me"), and authoritarianism (reversed items: "Liked me to make my own decisions", "Let me decide things for myself", "Gave me as much freedom as I wanted").…”
Section: Methodsmentioning
confidence: 99%
“…The original PBI scale comprises of 25 items, an abbreviated version of the PBI, constructed by the authors of the article, consisted of 9 items. The abbreviated version was developed according to Kendler's three-factor solution and the parameter estimates of each item (Tsaousis et al, 2012). The three items with the highest parameter estimates were selected for each factor: care ("Spoke to me in a warm and friendly voice", "Enjoyed talking things over with me", "Frequently smiled at me"), protectiveness ("Tried to control everything I did", "Tried to make me feel dependent on her/him", "Was overprotective of me"), and authoritarianism (reversed items: "Liked me to make my own decisions", "Let me decide things for myself", "Gave me as much freedom as I wanted").…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent research has confirmed the threefactor nature of the PBI in various populations, including children (Tsaousis, Mascha, & Giovazolias, 2012). While many studies concur on the three-factor model (i.e., Terra et al, 2009), various studies have suggested that for eastern populations such as Japan and China, a four-factor model provides better fit (i.e., Liu, Li, & Fang, 2010;Suzuki & Kitamura, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…At the same time, there are no theoretical prerequisites for a five-factor solution (e.g., Tsaousis et al, 2012).…”
Section: Exploratory Factor Analysismentioning
confidence: 99%
“…In order to obtain more accurate estimates of parent-child relationships, assessments of both parents and a child are necessary. Indeed, several studies of the family environment emphasize the low degree of agreement between the scores of mothers and children who filled out the same psychodiagnostic tool with correlation coefficients from 0.11 to 0.41 for younger adolescents (Tsaousis et al, 2012). According to some experts, the perception of the child by the parents is informative for understanding the relationships in the parent-child system (for example, Deater-Deckard et al, 2009).…”
Section: Introductionmentioning
confidence: 99%